KONTRIBUSI PROGRAM KAMPUNG BANTAR DALAM PENINGKATAN KESADARAN BERSIH, AMAN, DAN BELAJAR MASYARAKAT (Studi tentang Efektivitas Kepemimpinan Walikota Jambi) - Samsu, Samsu (At-Ta`lim, 2016)
This article aims to determine the importance of Kampung Bantar Program initiated by the government of Jambi city and its impact in increasing awareness is clean, safe, and public learning in Jambi city. The Kampung Bantar Program can be seen from the side view and publicâs attitude towards their impact for Jambi city. The theoretical framework was developed based on research; 1) The publics view of Kampung Bantar Program, 2) publicâs attitudes towards Kampung Bantar Program, and 3) the impact of Kampung Bantar Program to increase awareness of clean, safe, and public learning.There are fifty one people as sample, they are one headmaster, five head of neighbourhood association (RT), and fourty one people as residents in Telanaipura, Kotabaru, and Alam Barajo districts. This study uses a mixed methods approach and research using quantitative data as main data, as well as qualitative data assupporting data. Data were analyzed using a regression to see the t-test, F-test, and R2 test to determine the contributions of tested variables.The results has shown that overall public perceptions on Kampung Bantar Program was at a stage of significant, R2 (0301) for (Ï> 0.05), on the other hand, peoples attitude toward the Kampung Bantar Program are also at significant scale R2 (0049) for (Ï > 0.05). As together, research also shows that the publicâs views and attitudes towards Kampung Bantar Program contribute/influence to increase awareness of clean, safe, and public learning in Jambi city that are in significant stage R2 (0309) for (Ï> 0.05). It can be concluded that the Kampung Bantar Program have a significant impact in increasing awareness clean, safe, and public learning in Jambi city..KeywordsKampung Bantar Program, clean, safe, and publicâs learning